Application of The Problem Based Learning Model to Improve Student’s Mathematical Problem Solving Ability of Class VIIIB SMPIT Al-Fityah Pekanbaru - Hidayah, Ayu Rahmah; Heleni, Susda; Siregar, Syarifah Nur (Journal of Educational Sciences, 2024)
The research was based on low mathematical problem solving abilities of students in class VIIIB SMP IT Al Fityah Pekanbaru. The number of students who achieved the maximum score before action in each indicators were 56% - 60%, 0%, 64%, and 32% - 72%. The purpose of this research was to improve learning process and increase students’ mathematical problem solving abilities. The research was carried out in 2 cycles by applying a problem- based learning model in relation and function material that consist of planning, action, observation and reflection. The aim is to improve the learning process and increase students' mathematical problem solving abilities. The data collection techniques used are observation techniques and KPMM test techniques. The number of students who achieved the maximum score after cycle I and cycle II there are 72%-76% and 84%-92% in understanding problems, 44%-48% and 76%-92% in planning problem solving, 40%-80% and 48%-76% in implementing the completion plan, 28%-60% and 40%-72% in interpreting the results obtained. Based on the results, it can be concluded that thePBL model is a learning model that can be applied effectively in increasing students' KPMM.